Effects of Personification of Voting in Presidential and Parliamentary Elections in Russia - Petr V. Panov (Антиномии, 2023)
When directly elected presidents have fairly strong power in relations with the government and parliament, presidential elections are perceived as elections of the first order. In addition, voting for presidential candidates is much more personalized. To a large extent, this explains why, in Russia, the candidate of the party of power receives much more support in the presidential election than the party of power in parliamentary ones. Some voters who support opposition parties in the parliamentary elections vote “strategically” and “personally” in the presidential ones, giving their votes to the incumbent. However, the question remains how evenly this trend spreads across different segments of the electorate of political parties. To answer it, a comparative analysis of the 2016 parliamentary and 2018 presidential elections was carried out. Empirically, the study is based on electoral and socio-economic data in the context of municipalities. The analysis carried out by the method of multilevel linear regression has exposed that the line “party of power versus opposition” is quite clearly expressed in the parliamentary and blurred in the presidential elections. Based on the results obtained, it is concluded that personalized voting has a key impact on the difference in the results of political parties and their candidates. At the same time, both the consolidation of voters around the incumbent and the loss of votes by the candidate of the Liberal Democratic Party of Russia (LDPR) affect different segments of the electorate approximately equally, that is, the specifics of the electorate of these parties in the presidential election is leveled but it remains. With regard to the Communist Party of the Russian Federation (CPRF), on the contrary, insufficient affiliation of its candidate with the party led to the fact that different segments of the electorate changed their preferences unevenly. The final part of the article outlines promising directions for further research.